PENGEMBANGAN INSTRUMEN PENILAIAN KOGNITIF DALAM PEMBELAJARAN TEMATIK TERPADU KELAS 4 SD - Erlin Prasetyo; Wahyudi Wahyudi (PIONIR: JURNAL PENDIDIKAN, 2020)
The purpose of this study is (1) to know how to develop cognitive assessment instruments in the thematic learning of grade 4 elementary school (2) knowingthe valid levelof cognitive assessment instrument development in grade 4 primary school thematic learning based on classical analysis of problem items. (3) know the practicality of the development of cognitive assessment instruments in the thematic learning of grade 4 elementary school based on classical analysis of problem items. This RnD research goes through a preliminary study phase, product development and product trials. The subjects of this study were grade 4 teachers and students of SD Negeri 03 Ampel Boyolali. The results of this study provide the results that (1) how to develop cognitive assessment instruments is to determine a theme, KI, KD, GPA, learning objectives, measuring instruments, grids, question points, validation tests, practicality tests, and determine a final product (2) Item instruments in the form of PG 20 and description consists of 5 questions. Based on validtests conducted by experts, which include integrated thematic material experts got a score of 78 % with the criteria "high". From linguists get a score of 90.9 % with a "very high" criteria. And from the assessment experts get a score of 78.5 % with the criteria "high". 3) The development of cognitive assessment instruments in integrated thematic learning of 4SD classes through practicality tests obtained 84% teacher response results with "high" criteria. From the response of the questionnaire students with a total of 11 children scored 89.2 % with the criteria "high". Of all the percentage results of the development of cognitive assessment instruments in integrated thematic learning deserves to be used as an evaluation of grade 4 learning on the theme of 6 ideals sub-theme 1 me and my ideals.